SIGNIFICANCE TEST CONTROL IN THE EVALUATION OF FOREIGN STUDENTS’ KNOWLEDGE IN THE STUDY OF HUMAN ANATOMY IN HIGHER MEDICAL UNIVERSITIES - Міськів, В.А. (World of Medicine and Biology, 2014)
Article is devoted to the actual problem of test control of foreign students in the study of human anatomy in higher education medical universities. It was analyzed advantages and disadvantages of test control of students’ knowledge. and the establishment to use a test control of knowledge, allows you to create effective models of student assessment with current approaches and challenges of studying human anatomy. Test control is used to set the level of achievement of academic groups and individual students, the analysis of the various forms and methods of teaching, the final evaluation.